Islamic Humanism as the Basis for Character Formation in Modern Education - Wafda Sabilla; Abdul Khobir; M. Tegar Husain; M. Fadlullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of science and technology in the current era has resulted in significant transformations in the world of education, but often shifts attention to intellectual achievement (IQ) without paying attention to the formation of moral and spiritual character. This situation requires a change in the educational paradigm to balance the development of intelligence and ethical values. This study aims to explore in depth the principles, concepts, and relevance of Islamic humanism to the formation of student character, as well as its application in the context of modern education. The methodology applied is a literature review with an analytical-philosophical approach to analyze the concept of Islamic Humanism as a philosophical basis in education. The research findings indicate that Islamic humanism, which emphasizes humanitarian values based on Islamic teachings, serves as a foundation of values that align the development of science with faith and morality. This paradigm is relevant for: 1) Internalizing moral values amidst technological advancements, 2) Avoiding moral crises and the loss of humanity, and 3) Strengthening student identity. The conclusion confirms that Islamic humanism is an important philosophical basis for developing students into perfect human beings who are intellectually superior, have noble character, and have good morals.